(untitled) (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT The study has the purpose to indicate the presence of folkmidia in the regional television program Revista de Sábado, by the Rede Globo affiliate TV TEM. From the conclusion that the popular culture does not have defined boundaries and circulates widely among other cultures, through the globalization and the media, it was observed that the program publicizes the popular culture from the state of São Paulo through the appropriation of its expressions, thus acting like a folkmidia vehicle. Based on the classes of folkcommunication developed by Luiz Beltrão and José Marques de Melo, 13 episodes of Revista de Sábado broadcasted during the period of June to September 2014 were analyzed, and it was proved that the folkmidia subject was included among other themes explored by this program. KEY-WORDS Folkcommunication. Folkmidia. Revista de Sábado. Regional television